Acute Effect of Whole-Body Vibration in a Female Dog with Metritis - dos Santos, Ivan Felismino Charas; Rahal, Sheila Canevese; Freire, Lívia; Teixeira, Carlos Roberto; Inamassu, Letícia Rocha; Mamprim, Maria Jaqueline; Gomes, Mayara Viana Freire; Tannus, Filipe Carrari Isaac (Acta Scientiae Veterinariae, 2017)
Background: Whole-body vibration is a modality of exercise used in humans for therapeutic purposes or to increase physical performance. In veterinary medicine there are only a few reports on the use of this technology. The Whole-body vibration derivate from vibrating rhythmic movements caused by vibrating platforms. Vibrating platforms are used over 30 years in the treatment and prevention of injuries and other debilitating conditions in humans. This paper aims to describe the first report of a possible spontaneous opening of the cervix in a female dog with purulent metritis by Whole-body vibration using a platform vibration. Case: A sexually intact female American Pit Bull Terrier dog showed an acute effect after a single session of Whole- body vibration training. Physical examination and physiological parameters were within normal. Slight edema of the vulva was observed without signs of discharge. Complete blood cell count, serum chemistry and urinalysis yielded no significant abnormal findings. An enlarged uterus with content was observed during a transabdominal ultrasound. Despite this, a vibrating-platform session was performed during 15 min. A purulent vulvar discharge was observed 6 min. after Whole-body vibration exercise and remained continuous through session. After the Whole-body vibration exercise, the dog was treated with cephalexin for 15 days. Escherichia coli were isolated from vaginal discharge culture. Seven days after the Whole-body vibration session, no signs of vulvar edema or discharge were observed. A complete blood count, serum chemistry, urinalysis and uterus ultrasound showed no abnormalities. Ovariohysterectomy by minimally invasive technique was performed and was observed cysts in both ovaries. The patient was placed under general anesthesia withisoflurane/O2. The premedication used was carprofen, morphine sulphate, acepromazine and diazepam. The induction was with propofol. An open ventral midline celiotomy an ovariohysterectomy was performed. Ten days after the surgery the dog showed no abnormality. After recovered from anesthesia, the patient was discharged with meloxican and tramadol for postoperative inflammation and pain management. According to the owner, the immediate postoperative period was without any problems. The histopathology examination confirmed the presence of right ovary cystic and left uterine horn cystic, and uterine hyperplasia. Four months after the surgery, the dog returned for evaluation and the owner reported that patient had been doing well, with normal appetite, normal urination and defecation. Discussion: The Whole-body vibration is not yet fully understood and it is important that the patient is clinically evaluated before the Whole-body vibration session. Whole-body vibration is a modality of exercise used in humans for therapeutic purposes or to increase physical performance. Otherwise, in veterinary medicine there are only a few reports on the use of this technology. In the present report there were no clinical signs that indicated uterine infection. In human patients there are reports that showed any clinical signs of diseases before use the Whole-body vibration. The ultrasound exam had been done because was part of another study and showed an enlarged uterus. Therefore, the cervix opening after a single Whole- body vibration training may be considered a positive side effect of Whole-body vibration in female dogs since this event helped to diagnose the disease. Although, the effects of WBV on reproductive organs and endocrine system are not clear.